Road Congestion Level Detection using Image Processing in Matlab - Zheng, Leong Zi; A/L Eh Kan, Chessda Uttraphan (Evolution in Electrical and Electronic Engineering, 2020)
This project proposes a technique to determine the congestion level on the road using the image processing techniques. The image processing algorithm is written and simulated in MATLAB. The image processing techniques that are used in this work are image acquisition, image resizing, background subtraction using region of interest, adaptive thresholding and morphology operations. Pre-processing images that were captured from the traffic light junction are used as the image samples. The image of the road is divided into three regions which are level 1, level 2 and level 3. Experimental results show that the proposed technique is able to determine the level of road congestion accurately.